2009
DOI: 10.1007/s10751-009-0114-6
|View full text |Cite
|
Sign up to set email alerts
|

A quasi-continuous observation of the α-transition of Fe1 + x S by Mössbauer line tracking

Abstract: Mössbauer absorption line tracking methodology, under a constant velocity strategy, is used for a quasi-continuous observation of the α-transition on slightly non stoichiometric Fe 1+x S alloy. To this end, two strategies were applied: an intelligent absorption line tracking with a control algorithm that uses the data measured in the previous region to establish the position of the next partial spectral range; and a predetermined line tracking in which temperature evolution of a partial spectral region of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The voltage induced on a second coil is used to sense the resulting velocity to provide a control feedback loop. Due to this derivative behavior, their transfer function presents a cusp-like frequency response [1] centered at the mechanical resonance (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), where minimum attenuation and phase shift occur. An electrical resonance coincident with phase inversion (near 10 KHz) limits the gain margin to 40 dB.…”
Section: Operation Fundamentals and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The voltage induced on a second coil is used to sense the resulting velocity to provide a control feedback loop. Due to this derivative behavior, their transfer function presents a cusp-like frequency response [1] centered at the mechanical resonance (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), where minimum attenuation and phase shift occur. An electrical resonance coincident with phase inversion (near 10 KHz) limits the gain margin to 40 dB.…”
Section: Operation Fundamentals and Characterizationmentioning
confidence: 99%
“…temperature). Mössbauer Line Tracking (MLT) is a recently developed technique [15][16][17] designed to continuously locate a resonant absorption line during the experiment. In such application the counting efficiency is critical since it imposes dynamic limits.…”
Section: Performance and Applicationsmentioning
confidence: 99%
“…For example, selectiveness was essential to study recombination kinetics of the photodissociated Myglobin-CO [9] and nanocrystallization of Fe 73.5 Si 13.5 Cu 1 Nb 3 B 9 amorphous alloy [10]. More recently, we reported on some conceptual and practical advances of this approach accomplished by a set of experiments in which the Doppler energy was fixed at various values [11], or varied following a feedback [12] or a preset protocol, while the temperature was being changed. It was demonstrated that this method provides a higher degree of detail on material transformations than that obtained from the measurement of a limited number of conventional spectra.…”
Section: Introductionmentioning
confidence: 99%
“…1a. Long term stability of the system is an important factor, especially in high resolution experiments, being critical in constant-velocity applications [4][5][6][7][8][9]. In these cases transmission is recorded at a single energy for a long period of time.…”
Section: Introductionmentioning
confidence: 99%